Análise de Sustentabilidade em Projetos de Instalações de Produção de Petróleo - Pacheco, José Marcos Leite (2012)
A proposal for a global analysis of sustainability in projects related in oil facilities is presented. By considering economic, environmental and social aspects in the early stages of design, the suggested method is more comprehensive and can be used to complement the analysis commonly applied in the petroleum industry, such as: Study of Technical and Economic Feasibility; Environmental Impact Assessment and Risk Analysis. Several authors, associations, certification bodies and oil companies suggest different approaches to study sustainability in some specific activities (or industries). In this study, a checklist of significant sustainability aspects for the oil industry (surface facilities) was assembled. In addition, a matrix was developed to assess the sustainability items relevant to these projects. In this work, the checklist interacts with the matrix to perform a "Preliminary Analysis of Sustainability of the Enterprise" (APSE). This method allows the identification of aspects that contribute significantly to global sustainability. From this analysis, which includes economic, social and environmental aspects, is built a report that is used to analyze qualitatively and quantitatively the impact of the sustainability aspects of the project. In this analysis are identified items that strongly influence the economic, social or environmental aspects and evaluated alternatives that can increase the overall sustainability of the project. Finally, the alternatives that can be used to indicate the most sustainable option are identified. This method was applied in a project (design) of a small offshore platform. This case study shows how the APSE can contribute to the identification of sustainability initiatives for the enterprise. The results showed that relevant aspects can contribute decisively to global sustainability. Finally, it was observed that the proposed method can contribute to increased rates of sustainability, even after application of analysis commonly used in these projects